The Suspension of History in Contemporary Media Arts - Ross, Christine (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2008)
Abstract This article examines the temporal turn which has supported the development of media arts since the late 1980s: the exploration of and amplified preoccupation with the passage of time. Focusing on a specific case study (the installation work of French artist Melik Ohanian), it shows that the turn involves a range of perceptual strategies through which the temporal premises of classical modernity—history as progress and succession, what philosopher Yuval Dolev designates as “the becoming present of future events and then their becoming past”—are suspended, problematized and transformed in this very suspension. My claim is that the work of Ohanian, which evolves around the practice of simultaneity, is a key to this elaboration of alternative forms of historical narratives, in which futurity plays a renewed pivotal role.